Identification and Characterization of an Antibacterial Type VI Secretion System in the Carbapenem-Resistant Strain Klebsiella pneumoniae HS11286 - Liu, Lu; Ye, Meiping; Li, Xiaobin; Li, Jun; Deng, Zixin; Yao, Yu-Feng; Ou, Hong-Yu (Frontiers in Cellular and Infection Microbiology, 2017)
The type VI secretion system (T6SS) is a class of sophisticated cell contact-dependent apparatus with anti-eukaryotic or anti-bacterial function. Klebsiella pneumoniae is one of the most common bacterial pathogens with resistance to the carbapenem antibiotics. However, little is known about the antibacterial T6SS in K. pneumoniae. Using core-component protein searches, we identified a putative T6SS gene cluster on the chromosome of the carbapenemase-producing K. pneumoniae (CRKP) strain HS11286. Intraspecies and interspecies competition assays revealed an antibacterial function of the HS11286 T6SS. The phospholipase Tle1KP was found to be an effector protein that is transferred by T6SS. The overexpression of this effector gene in the periplasm caused severe growth inhibition of Escherichia coli. A sub-inhibitory concentration of β-lactam antibiotics stimulated the expression and secretion of the HS11286 T6SS and enhanced T6SS-dependent killing. It suggested that the antibiotics might be an impact factor for the T6SS secretion and antibacterial activity.